Primatas brasileiros: uma perspectiva da conservação no Brasil - FARIAS, Anailda Tertulino (2022)
Conservation initiatives there are increasingly needed in the face of the threats to primates. This research contributes in three ways to primate conservation in Brazil. First, we compiled and systematized the programs and projects distributed across the Brazilian regions (Midwest, Northeast, North, South and Southeast). Second, we analyzed land use and land cover in the distribution areas of four species of the genus Sapajus: Sapajus apella, Sapajus flavius, Sapajus libidinosus and Sapajus xanthosternos, using data from the National Aeronautics and Space Administration (NASA) and the United States Geological Survey (USGS) and provided by the Annual Mapping Project of Land Use and Coverage in Brazil (MapBiomas) and geoprocessing techniques. Third, we carried out measurements of the mangrove areas and the conservation units that are located within the species' distribution area. The results this research show that the largest number of conservation projects is concentrated in the Northeast and Southeast regions. The largest of conversion of forest areas in agricultural areas were those of S. flavius and S. xanthosternos. The areas of S. libidinosus and S. apella showed less anthropic disturbance. The species with the largest extension of mangrove area within the area of the IUCN polygons were S. libidinosus (53639,8 ha) and S. xanthosternos (48170,0 ha). The largest amount of conservation unit was identified in the distribution area of S. apella (109298486,7 ha) and S. flavius had the smallest area (212720,9 ha). The largest amount of area for the distribution area of S. apella may be a factor contributing to the this species to be classified as Least Concern (LC). Likewise, the smaller amount of protected area in the S. flavius distribution area may be negatively interfering with the conservation status of this species, which is currently classified as Endangered (EN) by the IUCN.